Analisis Faktor Penghambat Ekonomi Keluarga Nelayan Wilayah Pesisir Desa Bagan Percut, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang, Sumatera Utara - Agustina Rahayu Sianturi; Aprilia Zaeni Rapiah; Muhammad Najmul Fahmi; Vadillah Raihto Hutasuhut; Tumiar Sidauruk (Departement of Mathematics Education, 2024)
The aim of this research is to analyze the economic inhibiting factors for fishing families in the coastal area of ​​Bagan Percut Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. This research uses data analysis methods. Research results show that access to financial capital is one of the main challenges for fishermen in this region. The majority of fishermen depend on a loan system from local middlemen or